Response of some selected insecticides on neuropteran predator (Chrysopa lacciperda) of lac insect (Kerria lacca) - SINGH, J P; JAISWAL, A K; MONOBRULLAH, MD; BHATTACHARYA, A (The Indian Journal of Agricultural Sciences, 2011)
Laboratory bioassay was carried out during 2008 to evaluate some insecticides against larval instar of lac insect predator (Chrysopa lacciperda Kimmins) to develop suitable strategy for management of this serious neuropteran pest of Indian lac insect [Kerria lacca (Kerr)]. Seven safer insecticides, viz lambdacyhalothrin, carbosulfan, spinosad, indoxacarb, fipronil, alphamethrin and ethofenprox against lac insect, were evaluated for their bioefficacy against C. lacciperda Kimmins by topical application and exposing the insect on residual film of insecticides. Topical application of lambdacyhalothrin (0.005 and 0.008%), carbosulfan (0.02 and 0.03%), fipronil (0.005 and 0.01%), alphamethrin (0.005 and 0.01%), spinosad (0.02%), indoxacarb (0.02%), and ethofenprox (0.02%) exhibited 100% mortality of C. lacciperda within 24 hr of treatment. Fipronil (0.005 and 0.01%) and indoxacarb (0.02%) were found to be equally effective as cent per cent mortality was observed within 24 hr of treatment with both modes of treatment. In most of the treatments topical application of insecticides was found to be more effective as compared to exposure of insect on residual films. Hence, lambdacyhalothrin, carbosulfan, indoxacarb, spinosad, fipronil, alphamethrin and ethofenprox can be incorporated in IPM programmes while formulating strategy for effective management of this neuropteran predator of lac insect without having any adverse effect on lac insect. Fipronil is highly water soluble and hence may be cautiously used. Supervisory control of predators of lac is generally recommended.